Altered Expression of Signaling Genes in Jurkat Cells upon FTY720 Induced Apoptosis - Shaoheng He (International Journal of Molecular Sciences, 2010)
FTY720, a novel immunosuppressant, has a marked activity in decreasing peripheral blood T lymphocytes upon oral administration. Recent investigations suggest that the action of FTY720 on lymphocytes may result from its ability to induce cell apoptosis. However, the cell signaling mechanism involved in the FTY720-induced cell apoptosis remains unclear. Here we examined the apoptotic signal pathways mediated by FTY720 in Jurkat cells using microarray analysis. The results showed that FTY720 can induce Jurkat cell apoptosis in a dose and time dependent manner as assessed by cell viability, Hoechst 33258 staining, Annexin V binding and DNA fragmentation tests. cDNA microarray analysis showed that 10 µM of FTY720 up-regulated 54 and down-regulated 10 genes in Jurkat cells among the 458 apoptotic genes examined following the 6 h incubation period. At least five-fold increased expression of modulator of apoptosis-1 (MOAP-1), vascular endothelial growth factor (VEGF), tumor necrosis factor receptor-associated factors (TRAF 6), Caspase 2 (CASP 2), E2F transcription factor 1 (E2F 1) and Casapse 5 (CASP 5) genes was observed in microarray analyses; these results were confirmed with reverse transcription polymerase chain reaction (RT-PCR) examination. Our findings suggest that the mitochondria related signaling pathways are the key pathways involved in the FTY720-induced apoptosis in Jurkat cells. And our results provide a new insight into the mechanism of FTY720, which allows us to draw the first simple diagram showing the potential pathways mediated by FTY720.